Gibbons, Jessica. The Haunted Bar, St. John's. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Jessica Gibbons, a Grade 8 student at St. Peter's Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Jessica writes, "The story I chose is the haunted bar of downtown. The story takes place on a Sunday night when all the workers aren't working and they are in the basement telling jokes. The jokes they were telling were bad jokes about religion and God, that would be offensive to religious people, and right after one of the men told a really bad joke a big glass sign, that had been hanging securely from the ceiling with thick, strong chains, fell. The chains were torn off the ceiling and the sign fell, but never shattered. Later that night when he was walking past a mirror, he saw an old man in the mirror, but when he turned around, no one was there. It turned out that the old man had been murdered there many years ago, and still haunts it."